Bioaccumulation and enantioselectivity of type I and type II pyrethroid pesticides in earthworm. (February 2016) - Chang, Jing; Wang, Yinghuan; Wang, Huili; Li, Jianzhong; Xu, Peng
Abstract: In this study, the bioavailability and enantioselectivity differences between bifenthrin (BF, typeⅠpyrethroid) and lambad-cyhalothrin (LCT, type Ⅱ pyrethroid) in earthworm ( Eisenia fetida ) were investigated. The bio-soil accumulation factors (BSAFs) of BF was about 4 times greater than that of LCT. LCT was degraded faster than BF in soil while eliminated lower in earthworm samples. Compound sorption plays an important role on bioavailability in earthworm, and the soil-adsorption coefficient (Koc ) of BF and LCT were 22 442 and 42 578, respectively. Metabolic capacity of earthworm to LCT was further studied as no significant difference in the accumulation of LCT between the high and low dose experiment was found. 3-phenoxybenzoic acid (PBCOOH), a metabolite of LCT produced by earthworm was detected in soil. The concentration of PBCOOH at high dose exposure was about 4.7 times greater than that of in low dose level at the fifth day. The bioaccumulation of BF and LCT were both enantioselective in earthworm. The enantiomer factors of BF and LCT in earthworm were approximately 0.12 and 0.65, respectively. The more toxic enantiomers ((+)-BF and (−)-LCT) had a preferential degradation in earthworm and leaded to less toxicity on earthworm for racemate exposure. In combination with other studies, a liner relationship between Log BSAFS and Log Kow was observed, and the Log BSAFS decreased with the increase of Log Kow . Highlights: The bio-soil accumulation factors of bifenthrin was about 4 times greater than that of lambad-cyhalothrin. Lambad-cyhalothrin was more easily to be adsorbed in soil than bifenthrin. The bioaccumulation of lambad-cyhalothrin and bifenthrin in earthworm was enantioselective. A negative relationship between Log BSAFS and Log Kow was observed.